PRELIMINARY STUDIES ON THE EXPERIMENTAL RESEARCH OF THE EFFECTIVENESS OF THE USE OF GEO-INFORMATION MODELS IN THE AREA OF THE RIVER GOLIAMA KAMCHIA: PRELIMINARY STUDIES ON THE EXPERIMENTAL RESEARCH OF THE EFFECTIVENESS OF THE USE OF GEO-INFORMATION MODELS IN THE AREA OF THE RIVER GOLIAMA KAMCHIA - Andreev, Andrey; Dimova, G.; Petrova, P. (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Preliminary studies were necessary to ensure that the experimental research to demonstrate the effectiveness of the technology and the geo-information model were carried out in North-Eastern Bulgaria, along the river Goliama Kamchia.